Bentuk-Bentuk Kerjasama Dalam Kegiatan Bisnis Ditinjau Dari Perspektif Hukum Bisnis (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The purpose of this research is to find out how the legal rules regarding cooperation agreements in business activities are viewed from a business law perspective and what forms of cooperation in trade activities can be carried out by company management. By using normative juridical research methods, it is concluded: 1. The legal rules regarding cooperation agreements in business activities are reviewed from the perspective of business law, referring to Civil law, especially Article 1313 of the Civil Code, which states that "An agreement is an act in which one or more people bind oneself to one or more other people." So it is clear that agreements give rise to agreements, as well as the Trade Code and Indonesian laws and regulations in various forms of business entities. 2. Forms of cooperation in trading activities that can be carried out by company management, such as Mergers, Consolidations, Joint Ventures and Franchising. A merger is a combination of one or several business entities so that from an economic point of view they are one unit, without merging the merged business entities. Consolidation/merger between two or more business entities that combine themselves to merge into one and form one new business entity (consolidation). This aims to "make healthy" the business entity concerned or what is usually called restructuring. Joint Venture is an agreement between two or more parties to collaborate in an activity. Franchise Agreement in which one party is given the right to exploit and/or use the rights to intellectual property or inventions, or business characteristics owned by another party in exchange for compensation based on the terms and/or sale of goods and services. 1 Article. 2 Lecturers at the Faculty of Law, Unsrat, Manado. Master of Law.